The Fourth Amendment Protection Against Unreasonable Searches and Seizures and the French Experience - Boreil, Florence Sophie (1995)
Under the American approach to criminal justice, freedom of the individual is of the utmost importance. The American criminal justice system reflects a distrust of abuse of power and an emphasis on protection of personal freedom. However, the French take a contrary approach; under French law, freedom is achieved through the State. This paper examines the protection of individuals’ rights in American and French criminal procedure. Focus will be given to tracking the police investigatory powers in each country through searches and seizures, and the impact that those powers have on individuals’ rights. This paper will assert that the police investigatory function threatens individuals’ rights in both the United States and French